Integrasi Nilai-nilai Qurani dalam Desain Pembelajaran Modern Berbasis Student-Centered Learning untuk Penguatan Karakter Peserta Didik - Wahud, Fitria; Ahmad Farid; M. Makhrus Ali (Indo-MathEdu Intellectuals Journal, 2026)
This study examines the importance of integrating Qur’anic values into the design of modern learning based on Student-Centered Learning (SCL) for the reinforcement of students' character development. SCL, which places students at the center of the learning process, provides students with the opportunity to be more active in determining their learning direction. Qur’anic values that teach honesty, patience, empathy, and compassion can serve as a moral foundation in shaping students' character and noble conduct. This article highlights how the application of these values in learning can strengthen character formation, enrich learning experiences, and support holistic personal development. With this approach, it is expected that students will not only develop academically but also in social and moral aspects. Despite challenges in its implementation, collaboration between teachers, students, parents, and the community will strengthen the success of this integration in sustainable character education.